Convicting the Innocent in Belgium: Historical Exonerations and Their Contemporary Relevance - De Beuf, Tamara L. F.; Otgaar, Henry (The Wrongful Conviction Law Review, 2026)
Over the past three decades, awareness of wrongful convictions has surged, mobilizing an innocence movement that started in the United States and later expanded internationally. Research into wrongful convictions has contributed to this awareness and remains a crucial component in addressing the issue, also in democracies with ostensibly robust criminal justice systems. In Belgium, however, discussions on wrongful convictions have been limited since the issue is considered an anomaly in this country. This narrative is supported by the apparent absence of formal exonerations. Yet, our research demonstrates that people have been wrongfully convicted and exonerated by the Belgian criminal justice system, including for serious crimes. Drawing on the works of the late journalist Jos Cels, we conducted a comprehensive investigation into historical exoneration cases using open sources, such as the Belgian official gazette and digital newspaper archives. The findings include 28 exoneration cases spanning from 1830 to 1963, involving 33 exonerees. For a subset of these cases, we provide descriptive information and document the factors that allegedly contributed to the wrongful conviction, such as fraudulent forensic expert testimony, and report the grounds on which the wrongfully convicted people were eventually exonerated. This study confirms the existence of historical exonerations in Belgium and takes a first step in collating these seemingly overlooked injustices. Our findings resonate with research on contemporary wrongful convictions across the globe. Given the universal characteristics of wrongful convictions, these historical cases help raising awareness and foster understanding of modern-day injustices, among criminal justice professionals, irrespective of their jurisdiction.